Manajemen Program Peer Coaching di SDN 15 Koto Panjang Kota Solok untuk Pengembangan Profesionalime Guru Berbasis Spiritual - Juliandri Juliandri; Jamilus Jamilus (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
The development of teacher professionalism in elementary schools depends not only on pedagogical and cognitive competence but also on spiritual intelligence, which forms the foundation of integrity, work ethic, and teacher exemplarity in shaping students’ character. This study aims to describe the management of the peer coaching program at SDN 15 Koto Panjang Kota Solok as an effort to enhance teacher professionalism based on spiritual intelligence. The research employs a descriptive qualitative approach with data collection techniques including observation and data reduction. The findings show that the management of the peer coaching program is carried out through several stages: planning, which involves identifying teachers’ spiritual needs and integrating character values into lesson modules; implementation, which consists of conducting peer coaching sessions twice a month in a safe environment that allows teachers to share challenges, receive technical guidance, and gain spiritual reinforcement from the principal; and supervision, conducted through academic and non-academic monitoring to ensure consistent application of spiritual values and teacher professionalism in teaching practices. This program has been proven to contribute to improving instructional quality, teachers’ emotional resilience, and the strengthening of students’ character. Thus, peer coaching based on spiritual intelligence becomes an effective program for building teacher professionalism while addressing the challenges of moral degradation.   Keywords: peer coaching management, teacher professionalism, and spiritual based